Influence of LPL, APOAIV, APOAV, APOCIII and USF1 polymorphisms in a Portuguese population with clinical diagnosis of familial combined hyperlipidaemia - Santos, T. (2013)
This work was founded by project grant FCT PIC/IC/83333/2007